The Other Side of the Coin: Nurses’ Views and Behavior on Physical Restraint - Guvercin, Cemal Huseyin; Samur, Menevse; Gurkan, Kubra Pinar (Acta Bioethica, 2018)
Background: The physical restraint is a widely used practice that includes ethical problems. Analysis of the views and behaviors of nurses who apply physical restraint is important to determine the problems in the practice and to find solutions. Aim: To study the views and behaviors of the nurses who apply physical restraint. Research Design:The study was designed as a descriptive study. The data were collected using a questionnaire form and analyzed by chi-square tests. The study was conducted at a university hospital. The convenience sample consisted of 93 voluntary nurses. Findings: The decision to initiate/terminate the physical restraint is mostly (63.4%) made by the physician and the nurse together, and frequently (96.8%) wrist belts are used. While one-third of the nurses (33.4%) apply the restraint for more than 7 days, 21.4% never loosen the physical restraint. 28% of the nurses face resistance due to the restraint. 78.5% of the nurses obtain informed consent for the restraint whereas 51.6% believe that the consent is not necessary. Only 9.7% of the nurses record the practice to the patient observation chart. Additionally, there is a relationship between the unit, patients they cared for daily, years in the profession and the nurses’ views on restraint (p≤0.05). Conclusion: It is necessary to improve the nurses’ awareness and ethical sensitivity about physical restraint. Professional development of the nurses regarding physical restraint should be maintained continuously from the beginning of their undergraduate education. An institutional committee should be established to support decision-making and monitor the restraint processes.